Audit Fees as a Moderator of the Effects of Auditor Switching and Audit Quality on Audit Report Lag in Manufacturing Companies Listed on the Indonesia Stock Exchange - Andini Agustin Rachmat; Agus Setiawaty (Jurnal Akuntansi, 2026)
This study aims to examine the effect of auditor switching and audit quality on audit report lag with audit fees as a moderator. The sample determination used a purposive sampling technique and obtained 335 data from manufacturing companies from 2020-2024. The analytical tools used in this study were multiple linear regression analysis and moderated regression analysis using IBM SPSS Statistics 26 software. The results showed that auditor switching had a significant positive effect on audit report lag, audit quality had a significant negative effect, audit fees moderated the effect of auditor switching on audit report lag, and audit fees weakened the effect of audit quality on audit report lag.